Longitudinal 18F-FDG PET imaging in a rat model of autoimmune myocarditis. (8th August 2018) - Werner, Rudolf A; Wakabayashi, Hiroshi; Bauer, Jochen; Schütz, Claudia; Zechmeister, Christina; Hayakawa, Nobuyuki; Javadi, Mehrbod S; Lapa, Constantin; Jahns, Roland; Ergün, Süleyman; Jahns, Valerie; Higuchi, Takahiro
Abstract: Aims: Although mortality rate is very high, diagnosis of acute myocarditis remains challenging with conventional tests. We aimed to elucidate the potential role of longitudinal 2-Deoxy-2- 18 F-fluoro-D-glucose ( 18 F-FDG) positron emission tomography (PET) inflammation monitoring in a rat model of experimental autoimmune myocarditis. Methods and results: Autoimmune myocarditis was induced in Lewis rats by immunizing with porcine cardiac myosin emulsified in complete Freund's adjuvant. Time course of disease was assessed by longitudinal 18 F-FDG PET imaging. A correlative analysis between in- and ex vivo 18 F-FDG signalling and macrophage infiltration using CD68 staining was conducted. Finally, immunohistochemistry analysis of the cell-adhesion markers CD34 and CD44 was performed at different disease stages determined by longitudinal 18 F-FDG PET imaging. After immunization, myocarditis rats revealed a temporal increase in 18 F-FDG uptake (peaked at week 3), which was followed by a rapid decline thereafter. Localization of CD68 positive cells was well correlated with in vivo 18 F-FDG PET signalling ( R 2  = 0.92) as well as with ex vivo 18 F-FDG autoradiography ( R 2  = 0.9, P  < 0.001, respectively). CD44 positivity was primarily observed at tissue samples obtained at acute phase (i.e. at peak 18 F-FDG uptake), while CD34-positive staining areas were predominantly identified in samples harvested at both sub-acute and chronic phases (i.e. at 18 F-FDG decrease). Conclusion: 18 F-FDG PET imaging can provide non-invasive serial monitoring of cardiac inflammation in a rat model of acute myocarditis.